Concept and Typology of Discourse Personality - Khamdamova Dilafruz Malikjon kizi (Genius Publishing Group, 2022)
This article discusses the concept and typology of discourse personality. In linguistics, a "linguistic personality" is understood as a speech personality - a person as a native speaker, taken from the side of his ability to speech activity, i.e. a complex of psychophysiological properties of an individual, allowing him to produce and perceive speech works
Keywords: language; Linguistics; discourse; personality